Pengaruh Rasio Profitabilitas terhadap Harga Saham Industri Otomotif Yang Terdaftar di Bursa Efek Indonesia Periode 2013-2017 - Levely Dwi Yanti (Science of Management and Students Research Journal (SMS), 2020)
The research aims to purpuse of study to analyze the influenceof the ratio of profitability which is rate from Return on Asset, Return on Equity, NetProfit Margin and Gross Profit Margins are simultaneously and partial on stock price on automotive industry which is listed on the stock market.  The aims of this study are to analyze the effect of Profitability Ratio on  Price stock on automotive industry.This study was taken because there are still differences between the research study with each other and there is a difference between the real state of research study with each other and there is a difference between the real of research data with existing theory.The research methodology is descriptive and quantitative analysis methods. Data used is secondary data. The population become object in this research is automotive industries period of year of 2013-2017. Amount sample the used is the six (6)  industry company and still stand up during period of perception and also publicized of year of 2013-2017 by Indonesian Stock Exchange the analysis multiple regression, hypotesis test so determinant coefficient F test  and  t test. Results of multiple regression equation is Y = 3,796  +  0,014X1  +  0,283X2  +  0,930X3  + 0,296X4  + e. Profitability Ratio variabels simultaneously significant effect on Stock Prices. While partially has variable Net Profit Margin to effect of Stock Price.